أثر الضرائب على الإيرادات غير النفطية في المملكة العربية السعودية، دراسة قياسية: The Impact of Taxes on Non-Oil Revenues in the Kingdom of Saudi Arabia - محمد بن سعود المحيميد (Journal of North African Economies, 2025)
This study aims to measure the impact of current taxes on non-oil revenues in the Kingdom of Saudi Arabia. The descriptive analytical method was used to analyse the data for the period (2016: Q1– 2022: Q1). The results showed that there is a statistically significant relationship between the different types of taxes under study and non-oil revenues, with a variation of 41.3965 for the value of the F statistic test, which means that all types of taxes used in this study have a strong effect and can explain the variable of non-oil revenues. The study also concluded that the economic variables under study affect and explain 89.7% of the changes in total non-oil revenues. The effect of taxes is that if taxes on income, profits, capital gains, taxes on trade and transactions, and taxes on goods and services change by 1%, non-oil revenues will change positively on average by 0.369%, 0.413%, and 0.373%, respectively. The study also confirmed the existence of a long-term equilibrium relationship between non-oil revenues and all other taxes.